Therapy-based allied health delivery in residential aged care, trends, factors, and outcomes: a systematic review - Isabelle Meulenbroeks; Magdalena Z. Raban; Karla Seaman; Johanna Westbrook (BMC Geriatrics, 2022)
Abstract Background Allied health professionals in residential aged care facilities (RACFs) make important contributions to the physical and mental wellbeing of residents. Yet to date, health services research in RACFs has focused almost exclusively on nursing disciplines. This review aims to synthesise the current evidence on allied health services in RACF; specifically, how therapy-based allied health is delivered, what factors impact the quantity delivered, and the impact of services on resident outcomes and care quality. Methods Empirical peer-reviewed and grey literature focusing on allied health service delivery in RACFs from the past decade was identified through systematic searches of four databases and over 200 targeted website searches. Information on how allied health delivered, factors impacting service delivery, and impact on resident outcomes were extracted. The quality of included studies was appraised using the Mixed Methods Appraisal Tool (MMAT) and the AACODS (Authority, Accuracy, Coverage, Objectivity, Date, Significance) checklist. Results Twenty-eight unique studies were included in this review; 26 peer-reviewed and two grey literature studies. Sixteen studies discussed occupational therapy and 15 discussed physiotherapy, less commonly studied professional groups included dieticians (n = 9), allied health assistants (n = 9), and social workers (n = 6). Thirteen studies were assigned a 100% quality rating. Levels of allied health service provision were generally low and varied. Five studies examined the association between system level factors and allied health service provision, and seven studies examined facility level factors and service provision. Higher levels of allied health provision or access to allied health services, specifically physiotherapy, occupational therapy, and nutrition, were associated with reduced falls with injury, improved care quality, activities of daily living scores, nutritional status, and meal satisfaction in five studies. Conclusion Evidence on how allied health is delivered in RACFs, and its impact on resident health outcomes, is lacking globally. While there are some indications of positive associations between allied health staffing and resident outcomes and experiences, health systems and researchers will need commitment to consistent allied health data collection and health services research funding in the future to accurately determine how allied health is delivered in RACFs and its impact on resident wellbeing.